Taking a look at the calibration of a CCD detector with a fiber‐optic taper. Issue 2 (16th February 2016) - Alkire, R. W.; Rotella, F. J.; Duke, N. E. C.; Otwinowski, Zbyszek; Borek, Dominika
Abstract : A check of the flat‐field calibration of a CCD detector showed good agreement with the manufacturer's calibration. A position‐specific effect was detected that requires an additional correction to scale diffraction data properly. The source of this effect is uncorrectable using the flat‐field correction, leading to a modulation of sharp features. Abstract : At the Structural Biology Center beamline 19BM, located at the Advanced Photon Source, the operational characteristics of the equipment are routinely checked to ensure they are in proper working order. After performing a partial flat‐field calibration for the ADSC Quantum 210r CCD detector, it was confirmed that the detector operates within specifications. However, as a secondary check it was decided to scan a single reflection across one‐half of a detector module to validate the accuracy of the calibration. The intensities from this single reflection varied by more than 30% from the module center to the corner of the module. Redistribution of light within bent fibers of the fiber‐optic taper was identified to be a source of this variation. The degree to which the diffraction intensities are corrected to account for characteristics of the fiber‐optic tapers depends primarily upon the experimental strategy of data collection, approximations made by the data processing software during scaling, and crystal symmetry.